Pengaruh Lingkungan dan Kepuasan Kerja Terhadap Retensi Karyawan di First Love Patisserie Jakarta - Ishak, Riani Prihatini; Pratama, Yuda (Jurnal Ilmiah Pariwisata, 2021)
The purpose of this study was to find out the influence of work environment and job satisfaction towards employee retention. A questionnaire-based survey was distributed to Main Kitchen employees of the First Love Patisserie Jakarta. This study used descriptive, quantitative and verification approach with saturation sampling method. Data were analyzed using SPSS 25. The result showed : (1) there is a positive influence of work environment towards employee retention based on t-value with significant value < 0,005 and the regression coefficient has positive value; (2) there is a positive influence of job satisfaction towards employee retention which is showed by t-value with significant value < 0,005 and the regression coefficient has positive value; (3) there is a positive influence of work environment and job satisfaction simultaneously towards employee retention based on F value. Work environment and job satisfaction simultaneously influence employee retention showed by result of adjusted R2. The practical implications of this study are that work environment and job satisfaction play important role in supporting employee retention., where job satisfaction has a more positive influence than the work environment. Keywords: Work Environment; Job Satisfaction; Employee Retention, Patisserie